Monumentalisering av diasporaidentitet - Akman, Haci (Tidsskrift for kulturforskning, 2007)
From the 1980s a major migration to Europe took place from all parts of Kurdistan. Many of these migrants settled in Great Britain. About 25 000 Kurds live in London and the nearby areas, most of them are located in Hackney in the northern part of London. The intention of the article is to investigate how representation of Kurdish presence takes form within British society. The Kurdish Diaspora experience is complex and follows its own traditions. In this context, Diaspora is regarded as a political and cultural terrain wherein individual and collective memories are intertwined, put together again and reconstructed.